Approaches To the Interpretation of The Term “Argo” - Dilafruz Madazizova Xabibiloyevna (Zien Journals, 2022)
The article deals with the definition one of the phenomena of speech “argo”, based on the interpretation and analysis of local and foreign linguists. It explains the etymology of the word, its definitions and differences in its interpretation, as well as examples of how this term is used by members of society or social groups.
Keywords: interpret; арго; speech phenomenon; special phrase